2013
DOI: 10.1007/s11103-013-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid deficiency impairs ABA and IAA biosynthesis and differentially affects drought and cold tolerance in rice

Abstract: Plant responses to abiotic stresses are coordinated by arrays of growth and developmental programs. Phytohormones such as abscisic acid (ABA) and indole-3-acetic acid (IAA) play critical roles in developmental progresses and environmental responses through complex signalling networks. However, crosstalk between the two hormones at the biosynthesis level remains largely unknown. Here, we report that carotenoid-deficient mutants (phs1, phs2, phs3-1, phs4, and PDS-RNAi transgenic rice) were impaired in the biosyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 48 publications
4
72
4
Order By: Relevance
“…In the transcription factors interact with specific cis-acting elements existing in target gene promoters and regulate elaborate networks of drought-responsive genes and associated biochemical and physiological adaptations (yang et al 2014). Most of these adaptation responses are determined by several secondary messengers including some plant hormones (Qin et al 2011;Du et al 2013). Diverse sets of genes expressed in response to abiotic stress have been identified, and elucidation of their physiological or cellular roles in terms of either stress tolerance or sensitivity is a critical issue in current plant biology (Huang et al 2012;Jirschitzka et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the transcription factors interact with specific cis-acting elements existing in target gene promoters and regulate elaborate networks of drought-responsive genes and associated biochemical and physiological adaptations (yang et al 2014). Most of these adaptation responses are determined by several secondary messengers including some plant hormones (Qin et al 2011;Du et al 2013). Diverse sets of genes expressed in response to abiotic stress have been identified, and elucidation of their physiological or cellular roles in terms of either stress tolerance or sensitivity is a critical issue in current plant biology (Huang et al 2012;Jirschitzka et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of OsGH3-2 resulted in IAA-defi cient phenotype but resistant to cold stress (Du et al 2012 ). Similarly, carotenoid-defi cient rice phs1 , phs2 , phs3-1 , phs4 , and PDS-RNAi transgenic rice showed ABA and IAA biosynthesis defi ciency and showed similar phenotypes to OsGH3-2 overexpression plants against drought and cold (Du et al 2013b ). To conclude, it can be suggested that local auxin gradients link auxin responses and developmental changes under cold stress.…”
Section: Auxin and Cold Stressmentioning
confidence: 91%
“…However, the o verexpression lines showed greater tolerance to cold. Carotenoid-defi cient rice phs1 , phs2 , phs3-1 , phs4 , and PDS-RNAi transgenic rice showed ABA and IAA biosynthesis defi ciency and thus showed similar phenotypes to OsGH3-2 overexpression plants against drought and cold (Du et al 2013b ). Thus, a possible crosstalk modulated by ABA and IAA levels can affect drought responses of plants.…”
Section: Auxin and Drought Stressmentioning
confidence: 97%
See 2 more Smart Citations